White-backed Vulture Gyps africanus parental care and chick growth rates assessed by camera traps and morphometric measurements§. (31st August 2017) - Maphalala, Machawe I; Monadjem, Ara
Abstract : Persistent vulture declines across Africa are a cause for concern as the number of species threatened with extinction increases. The White-backed Vulture Gyps africanus was, until recently, considered abundant but has been declining rapidly in recent years due to various threats including decreasing food availability. We used camera traps to investigate nest attendance and food provision at the nests of White-backed Vultures in north-eastern Swaziland. Chick age influenced brooding behaviour of the parents, with a reduction in brooding time as the chick aged. Mean food provision rate by parents to the nestling was 0.7 bouts d −1, which was mostly delivered between 09:00 and 15:00. Contrary to expectations, provisioning rates did not increase with age of the chick despite both adults delivering food. The growth of chicks showed a curvilinear relationship with age for the first 100 d with the tarsus and bill reaching maximum length after 80 d. We recommend further research into the availability of food for breeding vultures in order to understand the emerging threat of declining food availability in Africa.